2021
DOI: 10.1097/mrm.0000000000000271
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa in the healthcare facility setting

Abstract: Pseudomonas aeruginosa is a Gram-negative pathogen that has become an important cause of infection in humans and can be associated with significant morbidity and mortality.Severe infections usually affect immunocompromised patients or those with chronic debilitating diseases. Its significance as a pathogen is exacerbated by its resistance to antibiotics, virulence factors and its ability to adapt to a wide range of environments. P. aeruginosa can have multiple intrinsic or acquired mechanisms of resistance, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…The spread of multidrug-resistant P. aeruginosa is particularly concerning. Over recent years, the worldwide spread of so-called "high-risk clones" of multidrug-resistant or extensively drug-resistant (MDR/XDR) P. aeruginosa has become a public health threat that needs to be urgently and decisively studied and managed (Spagnolo et al, 2021). The result of our study was closed to Al-Muhannak (2020) who found that Levofloxacin resistance 70% and similar to the result of Mohammed (2012) which was 69.3%.…”
Section: Discussionsupporting
confidence: 59%
“…The spread of multidrug-resistant P. aeruginosa is particularly concerning. Over recent years, the worldwide spread of so-called "high-risk clones" of multidrug-resistant or extensively drug-resistant (MDR/XDR) P. aeruginosa has become a public health threat that needs to be urgently and decisively studied and managed (Spagnolo et al, 2021). The result of our study was closed to Al-Muhannak (2020) who found that Levofloxacin resistance 70% and similar to the result of Mohammed (2012) which was 69.3%.…”
Section: Discussionsupporting
confidence: 59%
“…The spread of multidrug-resistant P. aeruginosa is particularly concerning. Over recent years, the worldwide spread of so-called “high-risk clones” of multidrug-resistant or extensively drug-resistant (MDR/XDR) P. aeruginosa has become a public health threat that needs to be urgently and decisively studied and managed [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare-acquired infections (HAIs), particularly in the critical care setting, have become increasingly common over recent decades, with Gram-negative bacterial infections presenting the highest incidence among them [ 1 ]. P. aeruginosa is one of the most frequent and serious causes of HAIs (e.g., respiratory and urinary tract, skin and soft tissues, ear and eye infections, and bacteriemia), which particularly affect immunocompromised patients [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors that contribute to the prevalence of these infections are the immunosuppressed status of the patients, the intrinsic resistance of P. aeruginosa to antimicrobials and disinfectants, and the prevalence of P. aeruginosa in the environment ( 2 ). Reservoirs for P. aeruginosa in the health care setting include moist surfaces such as sinks, faucets, drains, and medical equipment such as ventilators and endoscopes ( 3 6 ). Contamination of these surfaces is promoted by the propensity of P. aeruginosa to grow as biofilms, which have enhanced resistance properties that hamper decontamination efforts.…”
Section: Introductionmentioning
confidence: 99%